Producción y realización del proyecto de podcast: “Relatos a media voz” - Gomez Oroza, Daniela (2023)
The project consists of the realization of an audio fiction podcast that tells stories and legends from different parts of the country. With the format of an anthology series, we used a combination of narration, dialogue, atmospheres and sound effects. We also created a graphic and photographic identity for the podcast, both of which are displayed in the graphic pieces created for Spotify, and in the Instagram profile created for the diffusion of the project. The purpose is presenting stories of the Peruvian oral tradition (from the three regions of the country), in an immersive way, in order to bring them closer to an audience that is increasing their podcast consumption.